Effect of biofertilizer on growth and yield of carrot (Daucus Carota L.) plants in different latitudes of Lombok Island. Issue 4 (March 2021) - Nikmatullah, A; Khairunnisa, N; Amalia, R; Zawani, K; Sarjan, M
Abstract: Carrot is an important sub-tropical vegetable, and in the tropics it is commonly cultivated in high elevated mountainous areas to provide suitable environment (particularly temperature) for the optimum growth and productivity. Availability of suitable cultivation areas in Indonesia is limited while demand for the crop is increased. This research evaluated growth and yield of carrot in warmer temperature of lower land elevations, and examined capability of biofertilizer to increase growth responses and yield of the crop under sub-optimal temperature conditions. The first and second experiments were conducted in medium latitudes of 650 m above sea level (asl) and 550 m asl, while the third experiment was conducted in low land of 170 m asl. The experiments compared growth and yield of carrot plants with biofertilizer and without biofertilizer applications. The growth and yield of carrot were enhancing by biofertilizer application when planted in ca. 650 and 550 m asl. The biofertilizer-treated plants were taller, had a higher number of leaves, higher yield, carrot diameter and sweater than non-treated plants. In low land, however, biofertilizer bio-EXTRIM had no effect on plant growth and yield but the carrots in biofertilizer treated plants were sweeter than non-treated plants.